(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In this paper, we present a study of the Sommerfeld effect (Jump phenomena) in a nonideal mechanical oscillator, composed of an unbalanced DC motor, with limited powerÂ supply, coupled to the free end of cantilever beam and a shape memory alloy (SMA) actuatorÂ that works to damp the vibration. A nonlinear mathematical model for this system isÂ developed. The SMA wire constitutive model considers a nonlinear phase transformationÂ model. Numerical simulations shows the different aspects about the Sommerfeld effect,Â illustrating the influence of the different temperatures of the SMA actuator on the dynamic ofÂ the nonideal system. Keywords: Nonideal oscillator, Shape memory alloy, Jump phenomena